Recent Progress in Drug Release Testing Methods of Biopolymeric Particulate System - Yejin Kim; Eun Ji Park; Tae Wan Kim; Dong Hee Na (MDPI AG, 2021)
Biopolymeric microparticles have been widely used for long-term release formulations of short half-life chemicals or synthetic peptides. Characterization of the drug release from microparticles is important to ensure product quality and desired pharmacological effect. However, there is no official method for long-term release parenteral dosage forms. Much work has been done to develop methods for in vitro drug release testing, generally grouped into three major categories: sample and separate, dialysis membrane, and continuous flow (flow-through cell) methods. In vitro drug release testing also plays an important role in providing insight into the in vivo performance of a product. In vitro release test with in vivo relevance can reduce the cost of conducting in vivo studies and accelerate drug product development. Therefore, investigation of the in vitro-in vivo correlation (IVIVC) is increasingly becoming an essential part of particulate formulation development. This review summarizes the principles of the in vitro release testing methods of biopolymeric particulate system with the recent research articles and discusses their characteristics including IVIVC, accelerated release testing methods, and stability of encapsulated drugs.